Summary of Early Triassic carbon isotope records - Corsetti, Frank A.; Baud, Aymon; Marenco, Pedro J.; Richoz, Sylvain (Comptes Rendus - Palevol, 2005)
Much attention has been given to the negative δ13C anomaly nearly coincident with the Permian-Triassic boundary. New data indicate a stepwise decline in δ13C initiating before the Latest Permian extinction event followed by highly variable δ13C values during the remaining Early Triassic. δ13C values appear much less erratic as global metazoan diversity increased in the Middle Triassic. Given the previously unappreciated magnitude of isotopic change and the number of large δ13C excursions that occurred during the Early Triassic, catastrophic mechanisms like methane release/bolide impact become less attractive to explain the Early Triassic carbon isotopic record as a whole.
Keywords: Carbon isotopic record; Negative δC anomaly; Permian-Triassic boundary